Assessment of the Mandibular Buccal Shelf for Safe Miniscrew Insertion in Teenagers and Adults: A Cone-Beam Computed Tomography Study - Farahani, Mohammad; Eiffar, Husein; Namdari, Mahshid (Journal of Dental School, 2021)
Objectives This study assessed the mandibular buccal shelf (MBS) for safe miniscrews insertion in teenagers and adults. Methods Cone-beam computed tomography (CBCT) images of 30 teenagers and 30 adults were used to measure bone width and cortical bone thickness. Measurements were made at four sites buccal to the distobuccal cusp of mandibular 1st molar (D6), and mesiobuccal cusp (MB7), an area at the center of the bifurcation (Mid7), and distobuccal cusp (DB7) of mandibular second molar. Bone width was measured at four distances (4, 6, 8, and 10 mm) from the (CEJ). ANOVA was used for statistical analysis. Results The MBS was significantly different within each age group and in different age groups, tooth sites, distances from the CEJ, and cortical bone thicknesses (P<0.001). A significant difference was detected in bone width between the two age groups in D6 at all distances from the CEJ, MB7 and Mid7 at 4 mm and 6 mm, and DB7 at 4 mm from the CEJ (P<0.05). Cortical bone thickness was significantly different between the two groups at MB7, Mid7, and DB7 (P<0.05). Conclusion All distances from the CEJ at DB7 offered adequate bone width for safe miniscrew implantation. Mid7 showed suitable bone width at all distances from the CEJ in teenagers. In adults, miniscrews should be implanted at 6 mm from the CEJ. Miniscrews should be inserted in at least 8 mm distance from the CEJ at MB7. D6 is unsafe for miniscrew insertion in both groups at all distances from the CEJ.